Power System Operation Stability Assessment Method Based on Deep Convolutional Neural Network - Jinman Luo; Yuqing Li; Qile Wang; Liyuan Liu (EAI Endorsed Transactions on Energy Web)
INTRODUCTION:  For the assessment of power system stability, a power system assessment method based on a deep convolutional neural network is studied.